2018
DOI: 10.1016/j.cej.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Bioaugmentation of activated sludge with Achromobacter denitrificans PR1 for enhancing the biotransformation of sulfamethoxazole and its human conjugates in real wastewater: Kinetic tests and modelling

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…However, sorption to solids is expected to be significant for APIs with Log K ow greater than 4.0, for which APIs in this study were below, hence the aspect of resuspension by desorption is concluded to play a minor role (Das et al, 2017;Radjenović, Petrović, & Barcel , 2009;Thompson, Zhang, & Zhang, 2011). Nguyen et al (2018) also documented complete biotransformation of (Ac-SMX) and (SMX-Glu) in 6 hours of an aerobic reactor, with SMX concentration increasing within the first 4-6 hours. These findings greatly support the increase in SMX concentration by deconjugation and transformation of its metabolites.…”
Section: Occurrence and Partitioning Of Apis In The Wastewater Treatm...mentioning
confidence: 76%
See 1 more Smart Citation
“…However, sorption to solids is expected to be significant for APIs with Log K ow greater than 4.0, for which APIs in this study were below, hence the aspect of resuspension by desorption is concluded to play a minor role (Das et al, 2017;Radjenović, Petrović, & Barcel , 2009;Thompson, Zhang, & Zhang, 2011). Nguyen et al (2018) also documented complete biotransformation of (Ac-SMX) and (SMX-Glu) in 6 hours of an aerobic reactor, with SMX concentration increasing within the first 4-6 hours. These findings greatly support the increase in SMX concentration by deconjugation and transformation of its metabolites.…”
Section: Occurrence and Partitioning Of Apis In The Wastewater Treatm...mentioning
confidence: 76%
“…In an anoxic batch non-bioaugmented reactor test, no net removal of SMX was observed overall but SMX concentrations were observed to have increased in the first 6 hours simultaneously with deconjugation of Ac-SMX and SMX-Glu conjugates. SMX concentrations also remained constant thereafter for 16 hours (Nguyen et al, 2018). Compared to WWTP-1 and WWTP-2, WWTP-3, using both an anaerobic baffled reactor (ABR) and vertical wetland system, had the lowest HRT of 6 days, with a minimum HRT of 12 hours in the ABR.…”
Section: Occurrence and Partitioning Of Apis In The Wastewater Treatm...mentioning
confidence: 98%
“…In addition, various mathematical models have been developed to predict the fate and removal of antibiotics during biological wastewater treatment processes. Especially, activated sludge model for xenobiotics (ASM-X) has been previously developed to predict the fate of antibiotics (i.e., SMX, CIP, and TET). , More recently, the ASM-X framework has been used to identify the influence of different factors on antibiotics removal during wastewater treatment . Polesel et al showed that the variability in observed removal efficiencies could be associated with retransformation of conjugated metabolites back to parent antibiotics, SRT, adsorption on influent and effluent solids, influent–effluent dynamics and sampling strategy.…”
Section: Fate and Removal Of Antibiotics In Engineered Biological Tre...mentioning
confidence: 99%
“…De hecho, ciertos tratamientos biológicos y fisicoquímicos revierten varios metabolitos de los fármacos presentes en las aguas residuales hacia el antibiótico original, haciendo que las PTAR actúen como concentradores de algunas sustancias farmacéuticas (31,32) . Por ejemplo, en sistemas de tratamiento biológicos, los dos metabolitos principales del sulfametoxazol (N4acetil-sulfametoxazol y sulfametoxazol-N1glucuronido) experimentan la retrotransformación/desconjugación hacia el antibiótico padre, por acción enzimática a través de la escisión de la porción conjugada (35) .…”
Section: Fuente: Propiaunclassified